2010
DOI: 10.1002/ajp.20908
|View full text |Cite
|
Sign up to set email alerts
|

Sexual interference in the golden snub‐nosed monkey (Rhinopithecus roxellana): a test of the sexual competition hypothesis in a polygynous species

Abstract: Sexual interference (SI), which is defined as any disturbance directed to a mating pair by other individuals, has been reported in several primate species. It is widely suggested that successful harassers experience improved mating success by increasing their access to reproductive partners as well as by reducing the mating success of rivals. Although theories of primate sexual conflict highlight male intra-sexual mating competition, females also are reported to actively disrupt copulations between mating part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
0
15
1
6
Order By: Relevance
“…This indicates that the impacts of mating system on dispersal pattern may be affected by other ecological factors. With regard to the golden snub-nosed monkeys, its mating behavior is not limited to resident male of OMU, other resident males and bachelors also have chances to mate with OMU females26273637. As a result, both males and females were found to disperse within herd24.Even though we found some healthy females to leave their natal herd, their dispersal frequency was lower than that reported from a previous study based on genetic method29.…”
Section: Discussioncontrasting
confidence: 71%
“…This indicates that the impacts of mating system on dispersal pattern may be affected by other ecological factors. With regard to the golden snub-nosed monkeys, its mating behavior is not limited to resident male of OMU, other resident males and bachelors also have chances to mate with OMU females26273637. As a result, both males and females were found to disperse within herd24.Even though we found some healthy females to leave their natal herd, their dispersal frequency was lower than that reported from a previous study based on genetic method29.…”
Section: Discussioncontrasting
confidence: 71%
“…This reproductive strategy, in a sense, weakens competitive interactions between females for access to males and ensures that female relationships are not severely disrupted even if the adult sex ratio decreases in the non-mating season. Even under strong competition, female R. roxellana still possess other behavioral strategies that can be utilized to access the resident male such as female dispersal and sexual interference [38], [49], [74]. Our results suggested that for R. roxellana , such a market may undergo seasonal fluctuations.…”
Section: Discussionmentioning
confidence: 77%
“…Our study band contained over 140 individuals, most of whom were fully habituated to the presence of human observers and have been the focus of behavioral observations for the past 14 years [Qi and Yang, 2011]. Given that this golden snub-nosed monkey band has a home range of almost 20 km 2 and is extremely difficult to follow across steep ravines and mountain terrain, individuals are provisioned with approximately 200 g of corn and radishes per monkey per day over a period of 15 days per month.…”
Section: Study Site and Subjectsmentioning
confidence: 99%